1997
DOI: 10.1038/42076
|View full text |Cite
|
Sign up to set email alerts
|

A second catalytic metal ion in a group I ribozyme

Abstract: Although only a subset of protein enzymes depend on the presence of a metal ion for their catalytic function, all naturally occurring RNA enzymes require metal ions to stabilize their structure and for catalytic competence. In the self-splicing group I intron from Tetrahymena thermophila, several divalent metals can serve structural roles, but only Mg2+ and Mn2+ promote splice-site cleavage and exon ligation. A study of a ribozyme reaction analogous to 5'-splice-site cleavage by guanosine uncovered the first m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
127
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(137 citation statements)
references
References 23 publications
9
127
0
1
Order By: Relevance
“…38 Some large ribozymes use multiple metal ions but without cooperativity. [39][40][41] It was proposed that the VS ribozyme binds four Mg 2+ ions, but the affinity is very low (Kd = 17 mM). 42 We recently reported that the Tm7 DNAzyme employs three Ln 3+ ions cooperatively.…”
Section: Dy10a Is Highly Specific For Lnmentioning
confidence: 99%
“…38 Some large ribozymes use multiple metal ions but without cooperativity. [39][40][41] It was proposed that the VS ribozyme binds four Mg 2+ ions, but the affinity is very low (Kd = 17 mM). 42 We recently reported that the Tm7 DNAzyme employs three Ln 3+ ions cooperatively.…”
Section: Dy10a Is Highly Specific For Lnmentioning
confidence: 99%
“…in which an exogenous guanosine nucleophile (G) cleaves a specific phosphodiester bond of an oligonucleotide substrate (S)+ The well-characterized catalytic activity of this ribozyme provides a sensitive assay that can be used to probe its structure and conformation (Herschlag & Cech, 1990)+ Extensive mechanistic work and mutational analyses have provided a detailed model for active site interactions that are crucial for catalysis (Fig+ 1;Piccirilli et al+, 1993;Weinstein et al+, 1997;Strobel & Ortoleva-Donnelly, 1999;Shan & Herschlag, 1999;Shan et al+, 1999aShan et al+, , 2001Yoshida et al+, 2000, and refs therein)+ The tools developed in these studies Abbreviations: E denotes the Tetrahymena thermophila L-21 ScaI ribozyme; S denotes the oligonucleotide substrate with the sequence CCCUCUA 5 , without specification of modifications at the 2 ' -hydroxyl group (the individual oligonucleotide substrates used in this work are listed in Table 1); P denotes the oligonucleotide product with the sequence CCCUCU; G denotes the guanosine nucleophile, and G N denotes the guanosine analog in which the 2 ' -hydroxyl of G is replaced by a 2 ' -amino group+ M C refers to the metal ion at site C ( There is evidence for a conformational change within the active site upon binding of the oligonucleotide substrate and the guanosine nucleophile+ The presence of bound S at the active site increases the affinity of the ribozyme for the guanosine nucleophile, and vice versa (McConnell et al+, 1993;Bevilacqua et al+, 1994)+ Further, this coupling effect is dependent on temperature: S and G enhance the binding of one another only above 10 8C, whereas at lower temperature, the guanosine nucleophile can bind as strongly to the free ribozyme as to the E•S complex even when S is not bound (McConnell & Cech, 1995)+ This strong substrate binding in the absence of the other substrate at low temperature suggested that coupling does not arise from a direct interaction between the two substrates+ Rather, binding of S or G provides the energy for the change of the ribozyme to a conformation in which active site groups are better aligned to interact with the other substrate+ Below 10 8C, this conformation is apparently adopted by the ribozyme without the free energy from substrate binding, thereby allowing strong binding of S or G even in the absence of the other substrate (McConnell & Cech, 1995)+ What are the molecular interactions involved in this conformational change? The first clue came from the observation that the presence of bound oligonucleotide product (P) does not increase the affinity for G, even though P is more stably bound at the ribozyme active site than S; this indicates that the reactive phosphoryl group of S is required (McConnell et al+, 1993)+ The second clue came from the observation that coupling is lost when the 2 ' -OH of G is replaced by 2 ' -H, indicating that the 2 ' -OH of G is also involved (Li & Turner, 1997)+ Recently, a metal ion was identified that appears to coordinate both the p...…”
Section: Introductionmentioning
confidence: 99%
“…M A interacts with the 3′-anion of S (61). M B interacts with the 3′-moiety of G (62). A third metal ion, M C , interacts with the 2′-moiety of G (1,35).…”
Section: Determination Of the Rate Constant For The Chemicalmentioning
confidence: 99%